Results from single event effect tests with MIMOSIS-1. (1st April 2023) - Arnoldi-Meadows, B.; Andary, J.; Artz, O.; Baudot, J.; Bertolone, G.; Besson, A.; Bialas, N.; Bugiel, R.; Claus, G.; Colledani, C.; Darwish, H.; Deveaux, M.; et al.
Abstract: Being installed as close as 5.5 mm to the beam axis, the Micro Vertex Detector (mvd ) of the cbm experiment will be exposed to a sizable flow of heavy beam ions and nuclear fragments. The cmos Monolithic Active Pixel Sensor for the mvd, mimosis, must resist the related heavy ion impacts without permanent damage or frequent interrupt of operation as caused by single event effects (see ). We motivate the requirements on the sensor and introduce our concept for protecting the device against see s. Moreover, we report the results of a related test campaign carried out with the first full size sensor prototype, mimosis -1, and different heavy ion beams at gsi .